Acetylcholinesterase inhibition-based colorimetric determination of Hg2+ using unmodified silver nanoparticles. (1st December 2014) - Nanda Kumar, Dashananda; Rajeshwari, Ayyachamy; Alex, Sruthi Ann; Chandrasekaran, Natarajan; Mukherjee, Amitava
Abstract : A highly sensitive colorimetric sensor for Hg 2+ was developed with unmodified AgNPs using an enzyme-based indirect method. Abstract : A novel, enzyme-based, indirect detection method for mercury in aqueous solutions has been developed using unmodified silver nanoparticles. The enzyme acetylcholinesterase breaks down acetylthiocholine to thiocholine, which results in the crosslinking of the silver nanoparticles. The presence of mercury in solution prevents the aggregation of the silver nanoparticles by reversibly inhibiting the active site of the enzyme. The UV-visible absorption peak at 393 nm for the unmodified silver nanoparticles was found to decrease in the presence of acetylcholinesterase and acetylthiocholine. Upon adding mercury to the system, a concentration-dependent increase in the primary peak intensity at 393 nm was noted. The designed system was found to have good linearity ( R 2 = 0.9799) in the range of 10 to 50 nM of mercury with an excellent limit of detection of 1.18 × 10 −9 M in aqueous solution. This probe was successfully employed for the detection of mercury in spiked lakewater, groundwater, and seawater samples.